Simple Booking Training for Micro Small and Medium Businesses in Deli Serdang Regency, Tanjung Morawa District-A Bangun Rejo Village - Rizky Surya Andhayani Nasution; Sri Liniarti; M. Umar Maya Putra (Institute of Computer Science (IOCS), 2022)
Accounting is the process of recording, grouping, presenting data, and recording financial-related transactions where accounting serves as a measuring tool for the results of economic activities to convey information to various parties including management, investors, creditors, and regulators to provide information regarding the financial position” (Soemarso, 1983) The purpose of this community service is to find out the constraints faced by micro-businesses in compiling accounting books and to design a simple accounting bookkeeping system model that can help and facilitate micro-business owners in making good and neat financial reports. The results obtained from this training activity are able to increase the knowledge and skills of MSMEs in making simple bookkeeping so as to increase motivation at work. The conclusion is that simple bookkeeping training received a positive response from business actors as well as gaining knowledge and skills regarding new insights in running their business through simple bookkeeping or financial records that are easy to apply. The implication is that through simple bookkeeping training, business actors in Tanjung Morawa, Bangun Rejo Village, are able to understand how to be a good entrepreneur through financial records.